Case report: Axillary lymph node metastases from primary ovarian cancer: a report of two cases and literature review - Abdullah, Norlia; Rosly, Nadiah; Pauzi, Suria Hayati Md; Mustapha, Aida Widure; Arifuddin, Yulianty (Frontiers in Oncology, 2024)
Ovarian cancer is usually confined intraperitoneally. Distant metastases at presentation is unusual. Its spread via lymphatics is uncommon, and metastasis to axillary lymph nodes is very rare. We report two cases with presentation of axillary lymphadenopathy without breast involvement. Computed tomography scan identified the ovarian masses. Both had elevated Serum Ca 125. The first case had a Grade 2 ovarian endometrioid carcinoma. The second case had a high-grade serous ovarian carcinoma. These cases illustrate the rarity of axillary lymphadenopathy from ovarian cancer. It is important to identify the primary ovarian carcinoma in order to offer appropriate management. Despite surgery and chemotherapy, both succumbed within 3 years from diagnosis.